Do Urbanized Socioeconomic Background or Education Programs Support Engineers for Further Advancement?. Issue 4 (October 2021) - Alam, Gazi Mahabubul
Theoretically, education supports improving graduates' socioeconomic outcomes and careers by injecting citizenship values and making sure they are employable. Evidence confirms that socioeconomic background influences the level of education achieved which in turn greatly shapes the careers of graduates. Relevant knowledges and competencies are the fundamental parameters for career advancement. Ideally, education delivers the knowledge and competencies needed, and engineering is no different in this respect. The role of engineering education is crucial and to remove its associations of being a white-collar job, engineering education programs were developed to help working-class people enter this profession and advance their socioeconomic prospects. While socioeconomic backgrounds of engineering graduates can to some extent guide their career advancement the role of education is the major factor. A number of studies have examined the influence of socioeconomic backgrounds of graduates on career advancement, but none so far have been done for engineering education; particularly in a former British colonial setting. With this in mind the paper is the first to tackle this subject. Multiple techniques were used to collect the data and the findings confirm that engineering education and career advancement are not saliently linked. Not only education, but urbanized socioeconomic backgrounds do greatly govern the career advancement of engineers. A well targeted policy intervention may help engineering education to play a larger and more desirable role.